Effect of thermoformed tray architecture on transfer accuracy of lingual brackets: A prospective clinical study - Viet Anh Nguyen; Thi Quynh Trang Vuong; Thi Hong Thuy Pham; Thu Trang Pham; Viet Hoang (PLoS ONE, 2026)
Introduction This prospective clinical study assessed whether thermoformed transfer tray architecture influences in-vivo positional fidelity of lingual brackets during indirect bonding, and whether the resulting deviations remain within clinically acceptable limits. Methods A fully digital indirect bonding workflow was used. Bracket positions were planned on a virtual setup, and transfer trays were fabricated by thermoforming on 3D-printed models. Four tray designs were tested clinically under routine full-arch lingual bonding: a single-layer rigid tray (SR1) and three bilayer trays with a flexible inner liner of increasing thickness (BL1, BL2, BL3). After bonding, each bracket was digitized and superimposed onto the planned position using a local bracket-based coordinate system. Linear (mesiodistal, buccolingual, vertical) and angular (rotation, crown angulation, torque) deviations were calculated at the tooth level and compared across tray designs. Results All trays achieved clinically acceptable transfer accuracy. All linear deviations remained below 0.5 mm at the group level, and rotation and angulation were generally within 2.0°. SR1 showed the most favorable buccolingual and rotational control but required the longest chairside delivery time. BL1 achieved acceptable accuracy with a shorter delivery time. Increasing liner thickness (BL2, BL3) did not improve precision and was associated with greater deviation in several dimensions. Conclusion Tray architecture affected which axes were most vulnerable to error. Torque remained the least predictable dimension across all designs. Clinically, SR1 may be preferred in cases requiring strict control of rotation and buccolingual position, whereas BL1 offers a faster alternative for straightforward alignment without routine escalation to thicker bilayer trays.